Analisis Wacana Isi Pesan Iklan Politik Pemilihan Kepala Daerah DKI Jakarta Di Media Internet - Septiani, Redyta (Jurnal The Messenger, 2014)
Redyta Septiani, G.311.09.0042. Discourse Analysis of Political Advertising Message Jakarta Regional Head Election in Media Internet.Thesis : Study Programme S - 1 Communication Science University Semarang.The purpose of this study was to analyze the discourse on political advertising message content Jakarta Regional Head Election delivered via the Internet. This type of research is qualitative. The data in this study is qualitative data ( data that is without the numbers or numbers ), so the data is then analyzed substantive category by reference, reference, and scientific references ).The foundation of the theory used in this research adopt from Denis McQuail ( 2011) which states characterless new medi, not only the diversity and uncertainty in the future, but also because of the character that is postmodern. The question in this study is how the political message content on the internet.The method used in this study is a discourse analysis method proposed by Fairclough. Discourse analysis is used to analyze the languages used in a social phenomenon as well as simple things that exist in everyday society. Sources of data used in this study is the primary data source in the political ads on the internet, Secondary data source is data obtained from the study of literature, the website as a reference and a data amplifier, and mass media information associated with the object of writing this.It was concluded that the content of political advertising messages local election Jakarta Jokowi - Ahok on the internet have text isiya able to attract audiences of Internet users with short text.